Construction of meanings during life‐limiting illnesses and its impacts on palliative care: Ethnographic study in an African context. Issue 11 (2nd September 2019) - Agom, David A.; Neill, Sarah; Allen, Stuart; Poole, Helen; Sixsmith, Judith; Onyeka, Tonia C.; Ominyi, Jude
Abstract: Objective: Knowledge about how people make meaning in cancer, palliative, and end‐of‐life care is particularly lacking in Africa, yet it can provide insights into strategies for improving palliative care (PC). This study explored ways in which cancer patients, their families, and health care professionals (HCPs) construct meaning of their life‐limiting illnesses and how this impact on provision and use of PC in a Nigerian hospital. Methods: This ethnographic study utilised participant observation, informal conversations during observation, and interviews to gather data from 39 participants, comprising service users and HCPs in a Nigerian hospital. Data were analysed using Spradley's framework for ethnographic data analysis. Results: Meaning‐making in life‐limiting illness was predominantly rooted in belief systems. Most patients and their families, including some HCPs, perceived that cancer was caused by the devil, mystical, or supernatural beings. They professed that these agents manifested in the form of either spiritual attacks or that wicked people in society used either poison or acted as witches/wizards to inflict cancer on someone. These beliefs contributed to either nonacceptance of, or late presentation for, PC by most of patients and their families, while some professionals depended on supernatural powers for divine intervention and tacitly supporting religious practices to achieve healing/cure. Conclusions: Findings revealed that cultural and religious world views about life‐limiting illnesses were used in decision‐making process for PC. This, therefore, provided evidence that could improve the clinicians' cultural competence when providing PC to individuals of African descent, especially Nigerians, both in Nigerian societies and in foreign countries.